RASIONALITAS PENAFSIRAN IBNU âATHIYYAH - Karim, Abdullah (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2009)
Binyamin Abrahamov defines rationality as âtreating anyissues by using reason, but without giving reason priority.â Thus, interms of Qurâanic interpretation, rationality means using reason orijtihâd in interpreting the Qurâan without prioritizing the reason it self.For Ibn âAthiyyah, in addition to the existing authoritative reports of theprophetic tradition, reason is necessary in interpreting the Qurâan. Thisis because, the text of the Qurâan contains words whose meanings arespecific, ambiguous or even contradictory. However, this rationality ofinterpretation is only applied to the meaning of words or structure of theQurâanic sentences, but it does not include the use of analogy (qiyâs)employed in the methodology of Islamic law.